The family Bradyrhizobiaceae - Marcondes De Souza, Jackson Antônio [UNESP]; Carrareto Alves, Lucia Maria [UNESP]; De Mello Varani, Alessandro [UNESP]; De Macedo Lemos, Eliana Gertrudes [UNESP] (Springer Nature, 2013)
Bradyrhizobiaceae is a family of Rhizobiales order into the Alphaproteobacteria class that presents 12 genera including the type genus Bradyrhizobium. Phylogenetic analyses based on 16S rRNA sequences evoke a versatile family presenting a broad taxonomic affiliation with organisms from different environments like soil, plant, or animal hosts. Bacteria are pleomorphic with predominance of rod-shaped form. There is a diversity of phenotypic, metabolic, and ecological properties associated with each genus, and their participation in biogeochemical cycles is of extreme importance. Biological nitrogen fixation particularly performed by Bradyrhizobium is one of the most important ecological properties with potential application in agriculture, besides other diazotrophic members. In addition, the genus Afipia is clinically relevant once A. felis is a human pathogen causing the cat scratch disease. A lot of members of Bradyrhizobiaceae already had their genome completely sequenced which in turn corroborates their taxonomic classification. Considering that, taxonomy into Bradyrhizobiaceae will become better illustrated with advances in genomic projects applied to other members of this family.